In vitro digestion and stability assessment of β-lactoglobulin/riboflavin nanostructures - Madalena, Daniel A.; Ramos, Óscar L.; Pereira, Ricardo N.; Bourbon, Ana I.; Pinheiro, Ana C.; Malcata, F. Xavier; Teixeira, José A.; Vicente, António A. (Food hydrocolloids, 2016)
β-Lactoglobulin (β-Lg) is the major protein fraction of bovine whey serum and a primary gelling agent. β-Lg has a high nutritional value, is stable at low pH being highly resistant to proteolytic degradation in the stomach, besides, it has the ability of acting as an encapsulating agent. This study aims at assessing the ability of β-Lg nanostructures to associate a nutraceutical - i.e. riboflavin - and release it in a controlled manner throughout an in vitro gastrointestinal (GI) system. For this reason β-Lg nanostructures loaded with riboflavin were critically characterized in terms of their morphology (i.e. size, polydispersity, ζ-potential and shape) by dynamic light scattering (DLS) and transmission electron microscopy (TEM), and efficiency to associate to riboflavin through spectrofluorimetry. Furthermore, these nanocomplexes were evaluated in an in vitro GI model, simulating the physiological conditions. Stable β-Lg nanostructures were obtained at pH 6, of spherical shape, characterized by particle size of 172±1 nm, low polydispersity (i.e. PDI of 0.06±0.02), ζ-potential of −32±3 mV and association efficiency (AE) of 26±1 %. β-Lg nanostructures showed to be stable upon their passage throughout stomach (i.e. particle size, PDI and ζ potential of 248±10 nm, 0.18±0.03 and 18±3 mV, respectively). Concerning their passage throughout the intestine, such nanostructures were mostly degraded in the duodenum. Regarding riboflavin, a release of about 11 % was observed after their passage through stomach, while 35 %, 38 % and 5 % were the released percentages of the total riboflavin associated observed after passage through duodenum, jejunum and ileum, respectively. Hence, β-Lg nanostructures showed to be suitable carriers for riboflavin until the intestine, where their degradation occurs. β-Lg also showed to be structurally stable, under food simulant conditions (yoghurt simulant, composed of 3 % acetic acid), over 14 days, with a protective effect upon riboflavin activity, releasing it in a 7 day period. [Display omitted] •Production β-Lg nanostructures for riboflavin controlled release.•Assessment of β-Lg/riboflavin nanostructures during in vitro digestion.•β-Lg/riboflavin nanocomplexes showed to be stable in harsh stomach conditions.•β-Lg nanostructures are suitable carriers for riboflavin until the intestine.•β-Lg nanostructures showed to be stable over 14 days period.